Geospatial analysis of births with congenital disorders, Paraná, 2008-2015: ecological study - Márcia Helena de Souza Freire; Ana Paula de Morais Maia Barros; Luciano de Andrade; Oscar Kenji Nihei; Kátia Biagio Fontes (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: analyze the pattern of spatial distribution of the prevalence rate of births with congenital disorders and its relationship with social, economic, health care and environmental indicators in Paraná, Brazil, from 2008 to 2015. Method: ecological study with variables extracted from secondary banks, related to the births of children of mothers residing in Paraná, in two quadrennial (2008-2011 and 2012-2015). The analysis of the rates was performed with univariate spatial (Moran) and multivariate approach (Ordinary Least Squares and Geographically Weighted Regression). Results: the occurrence of congenital disorders presented a significant association (p<0.05) with: registration in primary care of pregnant women over 20 years of age; urbanization degree; consumption of pesticides; and balance of female formal employment. Conclusion/Final considerations: social, health care and environmental variables showed a non-stationary spatial pattern in the analyzed period and influenced positively and negatively the rates.